The mechanism of Laceyella sacchari FBKL4.010 produced tetramethylpyrazine in the liquid fermentation by comparative transcriptomic techniques - Wang, Xiaodan; Huang, Wu; Huang, Jin; Luo, Xiaoye; Nie, Mingbo; Jiang, Tao; Ban, Shidong; Li, Pei (Frontiers in Microbiology, 2024)
Tetramethylpyrazine (TTMP) is considered a crucial flavor component in Moutai-flavored liquor. Laceyeella sacchari FBKL4.010 (L. sacchari) is the dominant species found in Moutai-flavor Daqu, and this study aims to determine the mechanism by which L. sacchari produces TTMP during liquid fermentation of Moutai-flavor Daqu. The results of the liquid fermentation performance demonstrated a gradual increase in biomass over time, while there was a gradual decline in residual glucose content and pH value. Furthermore, analysis of volatile components revealed that liquid fermentation significantly enhanced the production of TTMP in Moutai-flavor Daqu, with the relative content of TTMP reaching 14.24 mg/L after 96 h of liquid fermentation. Additionally, to explore the synthesis mechanism of TTMP, we compared differentially expressed genes (DEGs) of L. sacchari between 24 and 96 h using comparative transcriptomic techniques. The results indicated that DEGs involved in isoleucine, valine, and leucine biosynthesis pathway were upregulated, while those associated with isoleucine, valine, and leucine degradation pathway were downregulated, suggesting that the valine, leucine, and isoleucine biosynthesis pathway primarily contributes ammonia for TTMP synthesis. The findings of this study present an opportunity for further elucidating the production process of TTMP in Moutai-flavor Daqu during liquid fermentation.